Effect of type of light source on the growth performance of Arabidopsis thaliana (Col-0) in UPM transgenic greenhouse - Karim, Mohd Shahrul Nizwanshah (2014)
Arabidopsis thaliana is a small flowering plant that is widely used as a model organism in plant biology especially in agricultural technology. Arabidopsis is a member of the mustard (Brassicaceae) family, which offers important advantages for basic research in genetics and molecular biology. It is important to identify the best source of light to be applied when growing Arabidopsis in the greenhouse based on their growth performance and for further uses in Arabidopsis research and seed production. The objectives of this experiment were to achieve one complete life cycle of Arabidopsis thaliana by using one media and to study the effect of source of light on the growth performance of A. thaliana (Col-0) in UPM Transgenic Greenhouse. The sources of light used in this study were Fluorescent light and LED light. The plantswere successfully grown in the greenhouse and produced hundreds of healthy seeds. However it took about 5 months which is longer than typical period (~2 months) to complete 1 life cycle. Through this study, it was found that there were significant effect of light source and significant difference between the 2 treatments that had been applied to the growth performance of A. thaliana in UPM Transgenic Greenhouse in term of leaf area and chlorophyll content. Treatment 2, which is the LED light is recommended to be used as the source of light in greenhouse for better growth of A. thaliana. The plant grown under the exposure of LED light showed the highest growth rate and highest value of chlorophyll content.